Pengaruh Demografi Dewan Direksi dan Kepemilikan Manajerial Dalam Mendeteksi Peluang Terjadinya Manipulasi Laporan Keuangan - Nur Aini Humairah; Tresno Eka Jaya R.; Marsellisa Nindito (Akuntansi, 2025)
This exploration aims to look into the impact of managerial ownership and board of directors demographics in detecting opportunities for manipulation of financial statements. The data type chosen is secondary data accessible on the Indonesia Stock Exchange website or each company's website and using quantitative methods. The population used is energy sector companies listed on the Indonesia Stock Exchange for 2019 - 2023. The results found in this research show that the age of the CFO has a significant influence in detecting opportunities for manipulation of financial statements. In contrast, other factors such as the age of the CEO, the gender of the board of directors, the educational background of the board of directors, and managerial ownership do not have a significant influence in detecting opportunities for manipulation of financial statements.